Complement modulation reverses pathology in Y402H‐retinal pigment epithelium cell model of age‐related macular degeneration by restoring lysosomal function. (20th August 2020) - Cerniauskas, Edvinas; Kurzawa‐Akanbi, Marzena; Xie, Long; Hallam, Dean; Moya‐Molina, Marina; White, Kathryn; Steel, David; Doherty, Mary; Whitfield, Phil; Al‐Aama, Jumana; Armstrong, Lyle; Kavanagh, David; et al.
Abstract: Age‐related macular degeneration (AMD) is a multifactorial disease, which is characterized by loss of central vision, affecting one in three people by the age of 75. The Y402H polymorphism in the complement factor H ( CFH ) gene significantly increases the risk of AMD. We show that Y402H‐AMD‐patient‐specific retinal pigment epithelium (RPE) cells are characterized by a significant reduction in the number of melanosomes, an increased number of swollen lysosome‐like‐vesicles with fragile membranes, Cathepsin D leakage into drusen‐like deposits and reduced lysosomal function. The turnover of C3 is increased significantly in high‐risk RPE cells, resulting in higher internalization and deposition of the terminal complement complex C5b ‐ 9 at the lysosomes. Inhibition of C3 processing via the compstatin analogue Cp40 reverses the disease phenotypes by relieving the lysosomes of their overburden and restoring their function. These findings suggest that modulation of the complement system represents a useful therapeutic approach for AMD patients associated with complement dysregulation. Abstract : Schematic presentation of autophagy‐lysosomal pathway dysfunction in Y402H‐AMD RPE cells and the impact of Cp40 in restoring the lysosomal function.